Leczenie chirurgiczne 14-letniej pacjentki z zatrzymanym zębem 22, po niepowodzeniu leczenia ortodontycznego = Surgical treatment of 14-year-old-patient with impacted upper left lateral incisor, after orthodontic treatment failed - Gnatek, Adrian; Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
Gnatek Adrian, Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Leczenie chirurgiczne 14-letniej pacjentki z zatrzymanym zębem 22, po niepowodzeniu leczenia ortodontycznego = Surgical treatment of 14-year-old-patient with impacted upper left lateral incisor, after orthodontic treatment failed. Journal of Education, Health and Sport. 2016;6(12):593-603. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.217615 http://ojs.ukw.edu.pl/index.php/johs/article/view/4104 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 22.12.2016. Leczenie chirurgiczne 14-letniej pacjentki z zatrzymanym zębem 22, po niepowodzeniu leczenia ortodontycznego Surgical treatment of 14-year-old-patient with impacted upper left lateral incisor, after orthodontic treatment failed Adrian Gnatek, Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze Adres do korespondencji: Adrian Gnatek Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: gnatekadrian@gmail.com tel. 42 675 75 71 Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Streszczenie: W artykule przedstawiono przypadek 14 - letniej pacjentki poddanej operacji usunięcia zatrzymanego zęba 22. Słowa kluczowe: zatrzymany ząb, chirurgia, znieczulenie ogólne, ekstrakcja, leczenie ortodontyczne. Abstract: The article shows the case of 14 years old patient, who was undergone the procedure of extraction of impacted upper left lateral incisor. Key words: impacted tooth, surgery, general anesthesia, extraction, orthodontic treatment.